Review of fire hazard analysis of ignalina nuclear power plant - Alejev, Aleksandr; Griškevičius, Mečislovas; Šukys, Ritoldas; Frith, Ian; Norta, Antti (Journal of Civil Engineering and Management, 2004)
Fire safety is important throughout the lifetime of a plant, from design to construction and commissioning, throughout plant operation and to decommissioning. The article is the document that will present the review results of the documents by VATESI during licensing Unit 1, 2 and provides information how Ignalina NPP to meet State requirements and international recommendations to achieve and maintain satisfactory fire safety. Fire hazard analysis of operation RBMK‐1500 type reactor is done for first time in the world practice.First Published Online: 14 Oct 2010